Social Skills Training (SST) untuk Peningkatan Keterampilan Sosial Pada Orang dengan Schizophrenia - Saulin Titin Liana; Kamsih Astuti; Kondang Budiyani (LPPM Universitas Proklamasi 45, 2018)
Schizophrenia causes the patients difficulties in building and maintaining social relationships. Furthermore, social dysfunction, which is one of the characteristics of schizophrenia disorder, is related to the lack of social skills. This study aims to find out social skills training towards the increase of social skills in schizophrenia i.e. listening to other, making request, expressing positive and negative feelings skills. The subjects of this study one male schizophrenia inpatients who are being treated in Balai Rehabilitasi Yogyakarta. This research applies A-B-A experiment design. Social skills are measured by conducting an observation and using behavior checklist instrument done by 3 rater. Based on the result of the analysis of the three rater is said ICC-consistency value is (ICC = 0.953), Sig = 0.000 which means that the result of rater 1 research, rater 2 and rater 3 assessment correlate to each other or are identical. In addition, the results of the visual inspection chart can be concluded that there is an increase in social skills on subjects with very low social skills, indicated by changes from phase A1 (8.5) to phase B (13.5) and to phase A2 (16.25) and follow up (17.5). This means that people with schizophrenia experience improved social skills after obtaining social skills training, indicating that social skills training interventions can improve social skills in people with schizophrenia. Key words: Social Skills for Schizophrenia, Social Skills Training